Volumetric Analysis of Endoscopic and Maxillary Swing Surgical Approaches for Nasopharyngectomy - Muhanna, Nidal; Chan, Harley; Qiu, Jimmy; Daly, Michael; Khan, Tahsin; Doglietto, Francesco; Kucharczyk, Walter; Goldstein, David P.; Irish, Jonathan C.; de Almeida, John R. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objectives/Hypothesis The endoscopic endonasal approach (EEA) for nasopharyngectomy is an alternative to the maxillary swing approach (MSA) for selected recurrent nasopharyngeal carcinomas (NPC). We compare the access between these approaches.Methods Three cadaver specimens were used to compare access volumes of the EEA and MSA. Exposure volumes were calculated using image guidance registration to cone beam computed tomography and tracking of accessible tissue with volumetric quantification. The area of exposure to the carotid artery was measured.Results The MSA provided higher volumes for access volume compared with the EEA (66.6 vs 39.1 cm3, p = 0.009). The working area was larger in the MSA (80.2 vs 56.9 cm2, p = 0.06). The exposure to the carotid artery was higher in the MSA (1.88 vs 1.62 cm2, p = 0.04). The MSA provided larger volume of exposure for tumors of the parapharyngeal space with exposure below the palate.Conclusions This study suggests that the MSA for nasopharyngectomy provides a larger volume of exposure. However, much of the increased exposure relates to exposure of the parapharyngeal space below the palate. The EEA provides adequate access to superior anatomical structures.
Keywords: endoscopic; maxillary swing; exposure volume; image guidance; nasopharyngectomy